Statistical Analysis of Youth Sports Implementation and Its Role in Sustainable Development - POPESCU, Maria Loredana; DOBRE, Florin; MANESCU, Cătălin-Octavian; GEORGESCU, Raluca Iuliana (European Journal of Sustainable Development, 2025)
In this context, analyzing the implementation of sports among young people becomes a pressing necessity. Various governmental and non-governmental initiatives and programs have been launched to encourage involvement in sports activities, but their effectiveness requires rigorous evaluation. The objectives of this paper are to identify the current level of participation in sports activities among young people, to analyze the factors that influence this involvement and to evaluate the effectiveness of existing programs. The study will use various statistical methods to analyze data collected from surveys and other relevant sources. The methodology will include both descriptive analyses and significance tests. The shape of the paper will encompass an evaluation of the specialized literature, description of the technique used, presentation and evaluation of the data, and very last conclusions. Through this research, I aim to contribute to a deeper understanding of how sport is implemented among young people and to provide recommendations based on statistical data for improving future policies and programs. Keywords: development, future, sports, youth